2016
DOI: 10.1590/s1518-8787.2016050005600
|View full text |Cite
|
Sign up to set email alerts
|

Work, malaise, and well-being in Spanish and Latin-American doctors

Abstract: OBJECTIVE To analyze the relations between the meanings of working and the levels of doctors work well-being in the context of their working conditions.METHOD The research combined the qualitative methodology of textual analysis and the quantitative one of correspondence factor analysis. A convenience, intentional, and stratified sample composed of 305 Spanish and Latin American doctors completed an extensive questionnaire on the topics of the research.RESULTS The general meaning of working for the group locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 17 publications
1
6
0
7
Order By: Relevance
“…These findings confirm a similar perception of the three collateral effects measured in healthcare professionals from institutions of four different Latin American territories. These findings are also in consonance with those reported in a recent study with physicians from Colombia, Brazil, Chile, and Venezuela (Ochoa and Blanch, 2016), but not with those preliminary reported with healthcare professionals from Argentina and other Latin American countries (Grau et al, 2009), where Argentineans showed a higher perception of burnout. According to those authors (Grau et al, 2009), differences observed between Argentinean and other Latin American healthcare professionals may be associated to differences in socio-economical conditions in those countries, but also can be the consequence of a methodological limitation: an unbalanced geographical distribution of the study sample (65% of the entire sample was composed by the Argentinean group, while the other 35% included data collected in ten Latin American countries).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…These findings confirm a similar perception of the three collateral effects measured in healthcare professionals from institutions of four different Latin American territories. These findings are also in consonance with those reported in a recent study with physicians from Colombia, Brazil, Chile, and Venezuela (Ochoa and Blanch, 2016), but not with those preliminary reported with healthcare professionals from Argentina and other Latin American countries (Grau et al, 2009), where Argentineans showed a higher perception of burnout. According to those authors (Grau et al, 2009), differences observed between Argentinean and other Latin American healthcare professionals may be associated to differences in socio-economical conditions in those countries, but also can be the consequence of a methodological limitation: an unbalanced geographical distribution of the study sample (65% of the entire sample was composed by the Argentinean group, while the other 35% included data collected in ten Latin American countries).…”
Section: Discussionsupporting
confidence: 84%
“…Despite this unique evidence reported is only from Mexican institutions, it is reasonable that a similar tendency may appear in institutions from other Latin American countries since medical education systems and social stereotypes associated to medicine and nursing are similar. In fact, findings reported in two recent studies on well being and work distress in Latin American institutions may offer new evidence in support of a common cultural perception of the physicians’ professional role (Grau et al, 2009; Ochoa and Blanch, 2016). In the first study (Grau et al, 2009), with Latin American healthcare professionals from Argentina, Uruguay, Mexico, Ecuador, Peru, Colombia, Guatemala, and El Salvador, differences in global perception of burnout were reported when the Argentinean group was compared to the other Latin American countries, but also when physicians were compared to the other healthcare professionals.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…But the results of empirical research that we have been carrying out with public attention services personnel, mainly from the worlds of the academy and the health and justice services [51][52][53][54], lead us to suspect that, in the empirical level, things are less clear than in the constructs: (a) In the context of interview and focus group, we have more difficulty distinguishing the indicators of engagement from workaholics than when we read texts on the subject. (b) The survey shows satisfied professionals above all for the material, technical, and social resources available to them and, at the same time, discomfort due to their job conditions regarding work overload and temporary pressure.…”
Section: Lights and Shadows Of The Work Engagement Modelmentioning
confidence: 99%
“…Sin embargo, el contexto socioeconómico y político de la última década no ha sido favorable para la implementación de estas intervenciones en el entorno sanitario. El incremento de los costes en salud, el aumento de las expectativas respecto a la sanidad, los avances tecnológicos, la crisis económica, los cambios en las políticas de financiación y de seguridad de los pacientes son factores que han determinado la necesidad de transformación de las rganizaciones anitarias , para o s 3,4 ser más ágiles y rentables, contener el gasto, contratar y retener profesionales excelentes, dar respuesta a las necesidades de los pacientes, mejorar la seguridad y la calidad asistencial y ser más eficientes. Algunos de éstos cambios han empeorado las CT, que comportan altos niveles de atención y concentración, elevada responsabilidad, sobrecarga y largos y desordenados horarios y turnos, situaciones que han contribuido a que los riesgos psicosociales en el entorno laboral estén más presentes .…”
Section: Introductionunclassified